2012
DOI: 10.5210/fm.v17i8.4071
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and goals after the Great East Japan Earthquake

Abstract: This paper examines the use of social media after the 2011 Great East Japan Earthquake. Based on media system dependency theory, the study focuses on the ways in which people used different types of social media to cope with a highly ambiguous situation created by the earthquake. A survey of Japanese university students revealed that the respondents used different forms of social media with different goals. Moreover, use of a particular social media type influenced the relative importance of social media for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Based on network analysis of over 300 million tweets after the 2011 Japan earthquake, Toriumi et al [60] found an abrupt increase in degree distribution of information by Twitter directly after the earthquake. Moreover, based on media system dependency theory, Jung [61] surveyed Japanese university students after the Fukushima accident. This study showed that the use and type of social media influenced people's attitude toward the Fukushima accident.…”
Section: Resultsmentioning
confidence: 99%
“…Based on network analysis of over 300 million tweets after the 2011 Japan earthquake, Toriumi et al [60] found an abrupt increase in degree distribution of information by Twitter directly after the earthquake. Moreover, based on media system dependency theory, Jung [61] surveyed Japanese university students after the Fukushima accident. This study showed that the use and type of social media influenced people's attitude toward the Fukushima accident.…”
Section: Resultsmentioning
confidence: 99%
“…Alarming information was also proliferating in Twitter (Li et al, 2014). People did not fully understand what had happened or what impact it would have for them personally (Jung, 2012). Many researchers concluded that the news of the meltdown had a devastating impact (Li et al, 2014;Ng and Lean, 2012;Pierpoint, 2011;Utz et al, 2013), generating widespread fear among the public in the absence of accurate authorized information.…”
Section: Pre-studymentioning
confidence: 99%
“…This had an impact, in particular, on TEPCO's Dai-ichi Nuclear Power Plant. During the earthquake, landlines and mobiles were out of operation (Jung 2012), leaving social media the least congested channel of communication. Therefore, social media interactions were frequent.…”
Section: Pre-studymentioning
confidence: 99%
See 2 more Smart Citations